IMPROVING STUDENT LEARNING MOTIVATION THROUGH THE UTILIZATION OF VIDEO MEDIA IN EDUCATION STUDENTS - Syaparuddin Syaparuddin; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
This research was motivated by the low learning motivation of class XI IPS.1 SMAN 6 Pinrang on Civics subjects. This can be seen from the behavior shown by students, students arriving late, not doing assignments, not paying attention to teacher explanations and being less active. Of the 36 students, only 3 students have high learning motivation. If calculated classically, the students' motivation to learn Civics subjects is 54.03%. This condition occurs as long as the PKn PBM teachers only use blackboards and worksheets. In order for student motivation to increase, teachers need to make a learning innovation. What the teacher can do is to use video as a learning medium. The acquisition of learning outcomes through the sense of sight is around 75%, through the sense of hearing about 13%, and through other senses around 12%. Formulation of the problem